2017
DOI: 10.1007/s00404-017-4515-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and genetic landscape of uterine leiomyomas: a current view over a common gynecological disease

Abstract: The new clues on genetics and epigenetics, as well as about the growth factors that control normal and pathological myometrial cellular biology may be of great help for the development of new effective and less invasive therapeutic strategies in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 109 publications
0
86
0
5
Order By: Relevance
“…Nonetheless, hysteroscopy plays a crucial role in the most challenging topics of women's health, from infertility diagnostic work-up [7,8] to post-menopausal abnormal uterine bleeding and uterine pathologies [9,10]. Currently, available technologies allow one to perform several diagnostic and operative procedures without the need for anesthesia and without any pain or distress for the patient [11,12]. For this reason, the role of dilatation and curettage to assess intrauterine pathologies and abnormal uterine bleeding tends to be no higher than office hysteroscopy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, hysteroscopy plays a crucial role in the most challenging topics of women's health, from infertility diagnostic work-up [7,8] to post-menopausal abnormal uterine bleeding and uterine pathologies [9,10]. Currently, available technologies allow one to perform several diagnostic and operative procedures without the need for anesthesia and without any pain or distress for the patient [11,12]. For this reason, the role of dilatation and curettage to assess intrauterine pathologies and abnormal uterine bleeding tends to be no higher than office hysteroscopy [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, PRa showed to be significantly unregulated in myoma of PreM compared to myoma of PostM women, which showed to be same in myometrium tissue ( Figure 1G, 3G). Those finding correlate with the fact that progesterone is cyclically elevated during the reproductive years, are significantly elevated during pregnancy, and are suppressed after menopause, however it is still very difficult to distinguishing the relative importance of estrogen versus progesterone [22,23].…”
Section: Discussionmentioning
confidence: 96%
“…Genetic defects are known to be the key points in tumor formation and a great amount of data has recently accumulated in this field. UF's cells contain multiple gene alterations that differentiate them from normal uterine muscle cells [23]. As in many other cases, a possible functional role of promoter deoxyribonucleic acid (DNA) methylation-mediated gene silencing has been proposed in the pathogenesis of those tumors [24].…”
Section: Uterine Fibroids-introduction Into Geneticsmentioning
confidence: 99%